Levels of hormones regulating appetite and energy homeostasis in response to a 1.5-Year combined lifestyle intervention for obesity - Kuckuck, Susanne; van der Valk, Eline S.; Scheurink, Anton J. W.; Lengton, Robin; Mohseni, Mostafa; Visser, Jenny A.; Iyer, Anand M.; van den Berg, Sjoerd A. A.; van Rossum, Elisabeth F. C. (Frontiers in Physiology, 2023)
Background: Weight loss can induce changes in appetite-regulating hormone levels, possibly linked to increases in appetite and weight regain. However, hormonal changes vary across interventions. Here, we studied levels of appetite-regulating hormones during a combined lifestyle intervention (CLI: healthy diet, exercise and cognitive behavioral therapy). Methods: We measured levels of long-term adiposity-related hormones (leptin, insulin, high-molecular-weight (HMW) adiponectin) and short-term appetite hormones (PYY, CCK, GIP, PP, FGF21, AgRP) in overnight-fasted serum of 39 patients with obesity. Hormone levels were compared between T0 (baseline), T1 (after 10 weeks) and T2 (end of treatment, 1.5 years). T0-T1 hormone changes were correlated with T1-T2 anthropometric changes. Results: Initial weight loss at T1 was maintained at T2 (-5.0%, p<0.001), and accompanied by decreased leptin and insulin levels at T1 and T2 (all p<0.05) compared to T0. Most short-term signals were not affected. Only PP levels were decreased at T2 compared to T0 (p<0.05). Most changes in hormone levels during initial weight loss did not predict subsequent changes in anthropometrics, except for T0-T1 decreases in FGF21 levels and T0-T1 increases in HMW adiponectin levels tended to be associated with larger T1-T2 increases in BMI (p<0.05 and p=0.05, respectively). Conclusion: CLI-induced weight loss was associated with changes in long-term adiposity-related hormones towards healthy levels, but not with orexigenic changes in most short-term appetite signals. Our data indicates that the clinical impact of alterations in appetite-regulating hormones during modest weight loss remains questionable. Future studies should investigate potential associations of weight-loss-induced changes in FGF21 and adiponectin levels with weight regain.